2014
DOI: 10.1186/2047-2994-3-17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nosocomial infections and anti-infective therapy in Benin: results of the first nationwide survey in 2012

Abstract: BackgroundData on nosocomial infections in hospitals in low-income countries are scarce and often inconsistent. The objectives of this study were to estimate the prevalence of nosocomial infections and antimicrobial drug use in Benin hospitals.MethodsAll hospitals were invited to participate in the first national point prevalence study conducted between 10–26 October 2012 using the protocol developed by the “Hospitals in Europe Link for Infection Control through Surveillance” (HELICS) project. Infection preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
68
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 16 publications
9
68
7
Order By: Relevance
“…In contrast to previous findings, Ahoyo et al (2014) showed that 65% of isolated microorganisms from nosocomial infected patients were Gram-negative, while only 30% were Gram-positive (Ahoyo et al, 2014). According to Vincent et al (1995), the infection causing micro-organisms, seen to inhabit ICUs more frequently were Enterobacteriaceae, S. aureus and Pseudomonas aeruginosa with a percentage of about 30 to 35%, while coagulase-negative staphylococci and fungi were reported to be 19 and 17%, respectively (Vincent et Sohn et al (2001).…”
Section: Etiology Of Nosocomial Infectionscontrasting
confidence: 46%
See 2 more Smart Citations
“…In contrast to previous findings, Ahoyo et al (2014) showed that 65% of isolated microorganisms from nosocomial infected patients were Gram-negative, while only 30% were Gram-positive (Ahoyo et al, 2014). According to Vincent et al (1995), the infection causing micro-organisms, seen to inhabit ICUs more frequently were Enterobacteriaceae, S. aureus and Pseudomonas aeruginosa with a percentage of about 30 to 35%, while coagulase-negative staphylococci and fungi were reported to be 19 and 17%, respectively (Vincent et Sohn et al (2001).…”
Section: Etiology Of Nosocomial Infectionscontrasting
confidence: 46%
“…Bloodstream infections occur at a frequency of 12% (Vincent et al, 1995). On the other hand, Ahoyo et al (2014) reported that the most recurrent nosocomial infections were UTIs (37.5%) followed by, intravascular catheter-associated (27%) and surgical site infections (19.2%). Lower respiratory tract infections or pneumonia was at 11.7%, while bloodstream infections were at 1.5%, and infections originating otherwise were about 3.1% (Ahoyo et al, 2014).…”
Section: Frequency Of Nosocomial Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study the most prevalent organism was A. baumannii with prevalence 37.2%, in accordance with our study Khashibai et al the highest frequent organism with a prevalence of 46.9% in the ICU, also, Neeta P Pradhan and et al reported that the respiratory infections in their study were most repeatedly related with isolates of Acinetobacter which had often multidrug-resistance profile (22). But in a study conducted in Morocco, the most prevalent organism was S. aureus (10). Edrinc and et al reported the most isolated organism was E.coli (3).…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO report, the prevalence of the nosocomial infection in developed countries is below 5%, however, in developing countries, this rate is different (6). In this study, the incidence of nosocomial infection is about 1.1%, which is not comparable to the global statistics in developing countries; a study conducted in Benin, in 2012, patients from the same ward were studied in the same day in each hospital for real estimation of nosocomial infection, and data showed that the prevalence rate of nosocomial infection was 19.1% (10). Other studies, especially from developing countries, reported the prevalence rate of 13.9% -17.9% (11,12).…”
Section: Discussionmentioning
confidence: 99%